Pengelolaan Kampanye Pengurangan Emisi melalui Konversi Motor Listrik - Naviel Abrar; ani yuningsih (UNISBA Press, 2024)
Abstract. One of the efforts made by the government, in this case the Directorate of EBTKE, to realize the transition to clean energy and support NZE is to carry out an electric motorbike conversion program. This research intends to find out the implementation of the emission reduction campaign from the aspect of managing the message and also determining the media whose reach is the audience of gasoline /BM vehicle users. The purpose of this research is to find out the public relations communication pattern in managing the emission reduction campaign through the conversion of electric motorbikes. This research uses qualitative research methods with a case study approach and uses a constructivist paradigm. The data collection techniques used in this research are FGDs, in-depth interviews, observation and also document and literature searches. The results of this study show the communication pattern of Ditjen EBTKE's public relations in managing the emission reduction campaign through electric motorcycle conversion. DG EBTKE focuses on managing campaign messages containing the urgency and benefits of this electric motor conversion to the public by collaborating with several units in the ESDM ministry to form a work team and utilizing conventional media such as radio as well as social media such as Instagram, Youtube, X & Facebook as a publication tool. EBTKE packages these contents by utilizing issues that are trending on social media so that the message looks more interesting and contemporary. However, the main media used is Instagram @djebtke. This campaign aims to support the clean energy transition in Indonesia. Abtrak. Salah satu upaya yang dilakukan oleh pemerintah dalam hal ini Direktorat EBTKE, untuk mewujudkan transisi ke energi bersih dan mendukung NZE adalah dengan melakukan program konversi motor listrik. penelitian ini bermaksud untuk mengetahui pelaksanaan kampanye pengurangan emisi dilihat dari aspek pengelolaan pesannya dan juga penetapan medianya yang jangkauannya adalah khalayak pengguna kendaraan bensin/BBM. Tujuan dari penelitian ini adalah untuk mengetahui pola komunikasi humas dalam pengelolaan kampanye penguragan emisi melalui konversi sepeda motor listrik. penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus dan menggunakan paradigma konstruktivis. Hasil dari penelitian ini menunjukkan pola komunikasi humas Ditjen EBTKE dalam pengelolaan kampanye pengurangan emisi melalui konversi motor listrik. Ditjen EBTKE fokus dalam mengelola pesan kampanye yang berisikan urgensi serta manfaat dari konversi motor listrik ini kepada masyarakat dengan berkolaborasi Bersama beberapa unit di kementerian ESDM membentuk sebuah tim kerja dan memanfaatkan media konvensional seperti radio juga media sosial seperti Instagram, Youtube, X & Facebook sebagai alat publikasi. EBTKE mengemas konten-konten tersebut dengan memanfaatkan isu yang sedang trending di media sosial agar pesan terlihat lebih menarik dan kekinian. Namun media utama yang digunakan adalah Instagram @djebtke. Kampanye ini bertujuan untuk mendukung transisi energi bersih di Indonesia.